Estimasi Temperatur Reservoir Panasbumi Menggunaakan Metode Geothermometer Pada Mata Air Panas Bitingan Dan Sipandu Area Panasbumi Dieng, Kabupaten Wonosobo, Provinsi Jawa Tengah - Yudhana, Waskita Murti Bambang Yudhana; Dianto Isnawan (ReTII, 2021)
Indonesia has a geothermal energy potential of 28,617 MegaWatt, which is 40% of the world’s total geothermal potential. One example of a volcano on the island of Java that has geothermal potential is the Telomoyo Volcano. This study aims to determine the geothermal system and to estimate the reservoir temperature using the Geothermometer Method. The results of the analysis show that the type of fluid is Bicarbonate Water. The results of plotting the concentrations of Sodium (Na), Potassium (K) and Magnesium (Mg) show that they are in the immmature water zone. The estimated temperature of the subsurface reservoir of Sipandu hot spring is Â±247.38Â°C, Bitingan hot spring is Â±195.21Â°C. The geothermal system in the study area is a liquid dominated system. Utilization of potential geothermal manifestations as hot springs and high temperature reservoirs that are good for developing into geothermal power plants.